2014
DOI: 10.1007/s12035-014-8848-9
|View full text |Cite
|
Sign up to set email alerts
|

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure

Abstract: Microwaves have been suggested to induce neuronal injury and increase permeability of the blood-brain barrier (BBB), but the mechanism remains unknown. The role of the vascular endothelial growth factor (VEGF)/Flk-1-Raf/MAPK kinase (MEK)/extracellular-regulated protein kinase (ERK) pathway in structural and functional injury of the blood-brain barrier (BBB) following microwave exposure was examined. An in vitro BBB model composed of the ECV304 cell line and primary rat cerebral astrocytes was exposed to microw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 47 publications
0
24
0
2
Order By: Relevance
“…In addition, previous studies have also showed that MEK/ERK inhibition may induce upregulation of TJs in undifferentiated cells, such as embryonic stem cells, intestinal epithelial cells (IEC-6, caco-2) or tumor cells [ 27 , 28 ]. Similarly, ERK activation may induce blood–brain barrier injury [ 29 ]. The related physiological processes are regulated by the transcriptional factors downstream of ERK.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have also showed that MEK/ERK inhibition may induce upregulation of TJs in undifferentiated cells, such as embryonic stem cells, intestinal epithelial cells (IEC-6, caco-2) or tumor cells [ 27 , 28 ]. Similarly, ERK activation may induce blood–brain barrier injury [ 29 ]. The related physiological processes are regulated by the transcriptional factors downstream of ERK.…”
Section: Discussionmentioning
confidence: 99%
“…This early insight has been corroborated by recent studies on various transmitter receptors in the brain such as N-methyl-D-aspartate receptors, dopamine and serotonin receptors (e.g. [148][149][150][151]. Some of these more recent studies also reported frequency window effects as well as intensity window effects on the neurodevelopment in the rat (152).…”
Section: Neurological Effects Of Extremely Low Frequency Electromagnementioning
confidence: 67%
“…As vascular invasion is suggested to be an early mechanism for turning cartilage into bone, these VEGF-expressing chondrocytes may promote the destruction of cartilage. However, angiogenic activity is not only determined by VEGF; p-ERK1/2 also stimulates angiogenesis [28]. Moreover, the Dll4-Notch signaling pathway is absolutely required for normal vascular development [29], and the perichondrial layer of the MCC is rich in both Notch ligands and various downstream facilitators of Notch signaling [30].…”
Section: Discussionmentioning
confidence: 99%